2011
DOI: 10.1002/ejlt.201000512
|View full text |Cite
|
Sign up to set email alerts
|

Determination of flavour loading in complex delivery systems by time‐domain NMR

Abstract: The determination of the flavour content of a newly developed encapsulation system based on yeast was attempted using time-domain NMR (TD-NMR) and compared to thermo gravimetric analysis (TGA). Flavour content as measured by TD-NMR is systematically higher than by TGA. The constant discrepancy between the two techniques is attributed to the presence of the phospholipidic membrane inside the yeast. These phospholipids also contribute to the NMR signal as was revealed by high field NMR studies under magic angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Using those as starting values for the bimodal fitting procedure and after having adjusted the parameter a representing the relative fraction in number of the two populations, usually consistent and reproducible fitting results were achieved. Contrary to YES samples no background signals of the GES matrix could be detected [35] and the values of R do not depend on the diffusion time D in the range between 50 ms and 800 ms (data not shown). The fitting values for Orange GES 1 and Orange GES 2 are reported in Table 2.…”
Section: Oil Droplet Sizing In Gesmentioning
confidence: 89%
See 3 more Smart Citations
“…Using those as starting values for the bimodal fitting procedure and after having adjusted the parameter a representing the relative fraction in number of the two populations, usually consistent and reproducible fitting results were achieved. Contrary to YES samples no background signals of the GES matrix could be detected [35] and the values of R do not depend on the diffusion time D in the range between 50 ms and 800 ms (data not shown). The fitting values for Orange GES 1 and Orange GES 2 are reported in Table 2.…”
Section: Oil Droplet Sizing In Gesmentioning
confidence: 89%
“…Hence, with standard, liquid-state high-field NMR methodology usually only the liquid part is observable, while the signals of the solid matrix are broadened beyond detection. Nevertheless, for YES it could be shown that the constituents of the phospholipid bilayer which is an integral part of the dried yeast cell wall are still sufficiently mobile to be detectable by high-resolution magic angle spinning NMR spectroscopy (HR-MAS) [35]. This background signal from the yeast matrix overlaps with the signal of the encapsulated oil in static NMR spectra and this is presumably the reason for the observed dependence of the droplet sizes in YES on the diffusion time D. Measurements of empty YES showed that the mobile lipid molecules show non-zero diffusion coefficients (D $ 10 À13 m 2 /s) which supposedly is due to slow diffusion along the phoshoplipid interface.…”
Section: Oil Droplet Sizing In Yesmentioning
confidence: 99%
See 2 more Smart Citations
“…1À2000 Fieber et al, 2011Hafner et al, 2011;Kalogeropoulos et al, 2010;Sillick and Gregson, 2012;Sosa et al, 2013. X-ray diffraction Non-invasive, non-destructive, high resolution, threedimensional structure can be seen.…”
Section: Glass Transition and Moisture Sorptionmentioning
confidence: 99%